PENGARUH MODEL PEMBELAJARAN BERBASIS VIRTUAL LABORATORY TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI GELOMBANG BUNYI DAN GELOMBANG CAHAYA - Nurfadlun Faradila Dalu; Tirtawaty Abdjul; Nova Elysia Ntobuo (Jambura Physics Journal, 2022)
Nurfadlun Faradila Dalu. 2019. The Effect of Virtual Laboratory- Based Learning Model on the Physics Learning Outcomes of Class XI Science Natural High School Student on Sound Wave and Wave Materials. Gorontalo Physics Education Study Program, Departement of Physics, Faculty of Mathematics and Natural Sciences Gorontalo State University. Guided: (I) Dr. Tirtawaty Abdjul,S.Pd, M.Pd., (II) Dr. Nova Elysia Ntobuo, S.Pd, M.Pd The purpose of this study was to determine differences in student physics learning outcomes that were taught with a Virtual Laboratory based learning model with student physics lerning outcomes using Real Experiment. The research method used was a quasi experiment with research design Posttest Only Control Group Design. The population of this study were all students of class XI SMA Negeri in North Gorontalo Regency in the academic year 2017/2018 and the study sample was taken by 2 schools using purposive sampling technique. Related data were analyzed by independent ttest. Theresult of data analysis obtained student learning outcomes that are taught using a Virtual Laboratory based learning model is superior to learning models that use Real Experiment.